(untitled) (ENTHYMEMA, 2019)
The contribution questions the relationship between psychoanalysis and poetry starting from the process of subjectivation that analytic practice offers to singularity: while the subject speaks during the analysis, something is written behind his shoulders. The relationship between the speaking body and the writing is thus investigated thanks to the poetic nature of the unconscious, at the core of which one meets the object of the drive and the silence of the word. Unlike the nihilistic or mystical outcome, the analytical experience invites us to write what cannot be said, replacing the ideal of poetic enunciation, grounded on the creative ego’s enunciation, with the weaving of the poem from which each is constituted.